2023
DOI: 10.3390/polym15061440
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Release of Platelet-Rich Plasma from Modified Nanofibers Studied by Advanced X-ray Photoelectron Spectroscopy Analyses

Abstract: Platelet-rich Plasma (PRP) is an ensemble of growth factors, extracellular matrix components, and proteoglycans that are naturally balanced in the human body. In this study, the immobilization and release of PRP component nanofiber surfaces modified by plasma treatment in a gas discharge have been investigated for the first time. The plasma-treated polycaprolactone (PCL) nanofibers were utilized as substrates for the immobilization of PRP, and the amount of PRP immobilized was assessed by fitting a specific X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…All these findings suggested that PRP was significantly incorporated into our layers. Our special curve fitting presented in previous work revealed that more than 50% of the surface is covered by PRP [26]. Hence, the surface of the nanofibers was successfully modified with the PRP proteins.…”
Section: Optimization Of Pcl Nanofibers Structure and Prp Immobilizationmentioning
confidence: 63%
“…All these findings suggested that PRP was significantly incorporated into our layers. Our special curve fitting presented in previous work revealed that more than 50% of the surface is covered by PRP [26]. Hence, the surface of the nanofibers was successfully modified with the PRP proteins.…”
Section: Optimization Of Pcl Nanofibers Structure and Prp Immobilizationmentioning
confidence: 63%
“…Due to the hydrophobic surface and, accordingly, the low value of free surface energy, effective attachment and proliferation of cells on the surface of polylactic acid and PLA/HA composite materials does not occur. This problem can be solved by exposing the surface of the composite to low-temperature plasma in a nitrogen flow [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%